Novel Synthetic Monothiourea Aspirin Derivatives Bearing Alkylated Amines as Potential Antimicrobial Agents - Norsyafikah Asyilla, Binti Nordin; Tchan, Wei Chai; Bee, Ling Tan; Ching, Liang Choi; Ainaa Nadiah, Abd Halim; Hasnain, Hussain; Zainab, Ngaini (Hindawi Publishing Corporation, 2017)
A new series of aspirin bearing alkylated amines moieties 1–12 were synthesised by reacting isothiocyanate with a series of aniline derivatives in overall yield of 16–56%. The proposed structures of all the synthesised compounds were confirmed using elemental analysis, FTIR, and 1H and 13C NMR spectroscopy. All compounds were evaluated for antibacterial activities against E. coli and S. aureus via turbidimetric kinetic and Kirby Bauer disc diffusion method. Compound 5 bearing meta -CH3 substituent showed the highest relative inhibition zone diameter against tested bacteria compared to ortho and para substituent. Furthermore, aspirin derivatives bearing shorter chains exhibited better bacterial inhibition than longer alkyl chains.